2023
DOI: 10.3389/fimmu.2023.1200456
|View full text |Cite
|
Sign up to set email alerts
|

Defining the pediatric response to SARS-CoV-2 variants

Abstract: The global population has been severely affected by the coronavirus disease 2019 (COVID-19) pandemic, however, with older age identified as a risk factor, children have been underprioritized. This article discusses the factors contributing to the less severe response observed in children following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including, differing viral entry receptor expression and immune responses. It also discusses how emerging and future variants could present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Across the symptomatic respiratory illnesses meeting our study criteria, we observed significant variation in the number of illnesses each participant experienced, as expected 2,4 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Across the symptomatic respiratory illnesses meeting our study criteria, we observed significant variation in the number of illnesses each participant experienced, as expected 2,4 .…”
Section: Discussionsupporting
confidence: 63%
“…While some participants recorded no respiratory illnesses despite strong adherence, others recorded up to 16 distinct illness events. TempTracker also captured the previously described inter-individual variability in terms of illness duration (range 1-13 days) and symptom manifestation 2,4 , even when comparing responses to the same virus. Within COCOON, we identified 26 household transmission events with significant variability between family members in their symptom development/duration and virus positivity, as has been reported in other household transmission cohorts 38,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation